Math, asked by rajrishit85, 7 months ago

using substitution method solve : 3x+y=13, x-3y+9=0​

Answers

Answered by sumatit967
0

Answer:

X = 5.5 bad y= -3.5

Step-by-step explanation:

first step :

3x + y =13

x-3y= 9

second step :

3 * ( X - 3y = 9 )

third step :

3x + y = 13

3x - 3y = 27

next step :

3x + y= 13

-3x + 3y = -27

next step :

0 + 4y = - 14

next step :

4y = -14

y = -14÷ 4

y = - 3.5

the value of y = -3.5

by puting the value of y in the first equation to find the value of X :

3x + (-3.5) = 13

3x - 3.5 = 13

3x = 13 + 3.5

3x = 16.5

X = 16.5÷ 3

X = 5.5

the value of X = + 5.5

Similar questions